Phage therapy: a revolutionary shift in the management of bacterial infections, pioneering new horizons in clinical practice, and reimagining the arsenal against microbial pathogens - Karn, Subhash Lal; Gangwar, Mayank; Kumar, Rajesh; Bhartiya, Satyanam Kumar; Nath, Gopal (Frontiers in Medicine, 2023)
The recent approval of experimental phage therapies by the FDA and other regulatory bodies with expanded access in cases in the United States and other nations caught the attention of the media and the general public, generating enthusiasm for phage therapy. It started to alter the situation so that more medical professionals are willing to use phage therapies with conventional antibiotics. However, more study is required to fully comprehend phage therapy’s potential advantages and restrictions, which is still a relatively new field in medicine. It shows promise, nevertheless, as a secure and prosperous substitute for antibiotics when treating bacterial illnesses in animals and humans. Because of their uniqueness, phage disinfection is excellent for ready-to-eat (RTE) foods like milk, vegetables, and meat products. The traditional farm-to-fork method can be used throughout the food chain to employ bacteriophages to prevent food infections at all production stages. Phage therapy improves clinical outcomes in animal models and lowers bacterial burdens in numerous preclinical investigations. The potential of phage resistance and the need to make sure that enough phages are delivered to the infection site are obstacles to employing phages in vivo. However, according to preclinical studies, phages appear to be a promising alternative to antibiotics for treating bacterial infections in vivo. Phage therapy used with compassion (a profound understanding of and empathy for another’s suffering) has recently grown with many case reports of supposedly treated patients and clinical trials. This review summarizes the knowledge on the uses of phages in various fields, such as the food industry, preclinical research, and clinical settings. It also includes a list of FDA-approved bacteriophage-based products, commercial phage products, and a global list of companies that use phages for therapeutic purposes.